Resolving spatial heterogeneities in exhumation and surface uplift in Timor‐Leste: Constraints on deformation processes in young orogens. Issue 6 (13th June 2014) - Tate, Garrett W.; McQuarrie, Nadine; van Hinsbergen, Douwe J. J.; Bakker, Richard R.; Harris, Ron; Willett, Sean; Reiners, Peter W.; Fellin, Maria Giuditta; Ganerød, Morgan; Zachariasse, Willem Jan
Abstract Although exhumation and surface uplift are important parameters in understanding orogenesis, the opportunity to measure both in close proximity is rare. In Timor‐Leste (East Timor), deeply exhumed metamorphic rocks and piggyback deepwater synorogenic basins are only tens of kilometers apart, permitting direct relation of uplift and exhumation by comparing micropaleontology to thermochronology interpreted through one‐dimensional thermal modeling. Foraminifera in two deepwater synorogenic basins suggest basin uplift from depths of 1–2 km to depths of 350–1000 m between 3.35 and 1.88 Ma. Thermochronologic sampling was conducted in the central mountain belt between these basins. Of four muscovite 40Ar/39Ar samples, one provides a reset age of 7.13 ± 0.25 Ma in the Aileu high‐grade belt that suggests ~9–16 km of exhumation since that time. Eighteen zircon (U‐Th)/He samples contain a group of reset ages in the Aileu Complex ranging from 4.4 to 1.5 Ma, which suggest exhumation rates of 1.0–3.1 mm/yr with 2.7–7.8 km of exhumation since these ages. Thirteen apatite (U‐Th)/He ages in the Gondwana Sequence range from 5.5 to 1.4 Ma, suggesting 1–2 km of exhumation and defining a pattern of exhumation rates (ranging from 0.2 to 1.3 mm/yr) that positively correlates with average annual rainfall. Seven apatite fission track samples display varying degrees of partial resetting, with greatest resetting where apatite (U‐Th)/He ages are youngest. Together, these data demonstrate extreme variability in surface uplift and exhumation over small spatial scales. We propose ongoing subsurface duplexing driven by subduction and underplating of Australian continental crust as the predominant driver for surface uplift and uplift‐induced exhumation.